2009
DOI: 10.1080/10926770903103099
|View full text |Cite
|
Sign up to set email alerts
|

Women's Use of Intimate Partner Violence against Men: Prevalence, Implications, and Consequences

Abstract: Evidence showing that women use intimate partner violence (IPV) against their male partners has existed since the 1970s when IPV was first systematically examined. This article discusses the various sources of prevalence rates of IPV by women against men, the dominant theoretical explanation for IPV in general, and its implications for female perpetrators and male victims in the social service and criminal justice systems, as well as the current evidence of the consequences of women's use of IPV to the men who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
1
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 51 publications
1
100
1
13
Order By: Relevance
“…For example, in their study on leadership, philosophy, and structure of 276 BIPs in 45 states, Price and Rosenbaum (2009) found that although offenders are not a homogeneous group, interventions are based on a "one-size-fits-all" model. Although money constrains possibilities, Price and Rosenbaum (2009) add to a chorus of scholars that advocate for culturally relevant treatment interventions (e.g., Almeida et al, 1998;Burnette, Ferreira, & Buttell, 2015;Cannon & Buttell, 2015;Eckhardt et al, 2013;Goldenson, Spidel, Greaves, & Dutton, 2009;Hamel, 2014;Hines & Douglas, 2009;Kernsmith & Kernsmith, 2009;Mauiro & Eberle, 2008). Rather, according to Eckhardt et al's (2013) extensive review of research on BIPs, gender reeducation is the predominant focus of treatment interventions because of the presumed notion that IPV is an extension of male dominance and control.…”
Section: State Standards and Intervention Programsmentioning
confidence: 99%
“…For example, in their study on leadership, philosophy, and structure of 276 BIPs in 45 states, Price and Rosenbaum (2009) found that although offenders are not a homogeneous group, interventions are based on a "one-size-fits-all" model. Although money constrains possibilities, Price and Rosenbaum (2009) add to a chorus of scholars that advocate for culturally relevant treatment interventions (e.g., Almeida et al, 1998;Burnette, Ferreira, & Buttell, 2015;Cannon & Buttell, 2015;Eckhardt et al, 2013;Goldenson, Spidel, Greaves, & Dutton, 2009;Hamel, 2014;Hines & Douglas, 2009;Kernsmith & Kernsmith, 2009;Mauiro & Eberle, 2008). Rather, according to Eckhardt et al's (2013) extensive review of research on BIPs, gender reeducation is the predominant focus of treatment interventions because of the presumed notion that IPV is an extension of male dominance and control.…”
Section: State Standards and Intervention Programsmentioning
confidence: 99%
“…Hines is critical of the lack of research comparing abused and non-abused men: much of the research has focussed on comparing abused men to abused women and concluding that they do not suffer to the same degree (e.g., Hines & Douglas, 2009). Men may be more likely to externalise their behavior (e.g., by using alcohol and drugs) and women to internalise theirs, indicating an unfair comparison (Hines & Malley-Morrison, 2001).…”
mentioning
confidence: 99%
“…Specifically, our study documented the occurrence of women's sexual IPV perpetration during pregnancy and, therefore, a need for future studies to replicate our findings and assess correlates and predictors of this type of IPV during pregnancy. Considering the negative consequences of IPV documented among both men and women (Hines & Douglas, 2009, the risk of IPV related victimization and injury that women incur when they perpetrate IPV (Abel, 2001;Hamberger, 2005;Sullivan, Meese, Swan, Mazure, & Snow, 2005), and the substantial risks for both mother and child associated with IPV during pregnancy and postpartum (Bailey & Daugherty, 2007;Flynn & Chermack, 2008;Goedhart, van der Wal, Cuijpers, & Bonsel, 2009;Morland, Leskin, Block, Campbell, & Friedman, 2008), our findings suggest that additional research is needed to determine the prevalence and scope of sexual IPV victimization and perpetration among expectant couples.…”
Section: Discussionmentioning
confidence: 99%